NON-VERBAL COMMUNICATION OF THE SIMPSONS MEMES IN “MEMES.COM” INSTAGRAM - Vivian Savenia Sumeisey; Rahmadsyah Rangkuti; Rohani Ganie (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
The research aims to identify the nonverbal communication especially kinesics aspect in the Simpsons memes in “memes.com” instagram. The nonverbal communications in the Simpsons memes convey the meme users’ emotions, feelings and messages through expressive actions. By analyzing the non verbal communication, the meme users are able to understand the meaning of the meme and the meme readers are able to understand what the memes senders try to communicate. The research was conducted by means qualitative descriptive analysis. The data of the research was the Simpsons meme and the source of data was “memes.com” instagram. The data collection was qualitative audio and visual material because the data is a picture. The sample of the research was forteen Simpsons memes. Facial expression, posture and gesture are the kinesics aspect that found in the Simpsons memes in “memes.com” instagram. The results of the researchwere one meme showed posture and gesture, two memes showed facial expression and gesture, three memes showed facial expression and posture, memes only showed posture and five memes showed the character’s facial expression in conveying the message.